2016
DOI: 10.1186/s13024-016-0084-5
|View full text |Cite
|
Sign up to set email alerts
|

Generation of aggregation prone N-terminally truncated amyloid β peptides by meprin β depends on the sequence specificity at the cleavage site

Abstract: BackgroundThe metalloprotease meprin β cleaves the Alzheimer’s Disease (AD) relevant amyloid precursor protein (APP) as a β-secretase reminiscent of BACE-1, however, predominantly generating N-terminally truncated Aβ2-x variants.ResultsHerein, we observed increased endogenous sAPPα levels in the brains of meprin β knock-out (ko) mice compared to wild-type controls. We further analyzed the cellular interaction of APP and meprin β and found that cleavage of APP by meprin β occurs prior to endocytosis. The N-term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
77
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(82 citation statements)
references
References 75 publications
5
77
0
Order By: Relevance
“…Sporadic PD accounts for more than 90% of PD cases (Lang and Lozano, 1998), and only less than 10% of familial PD cases are caused by monogenic mutations (Benitez et al, 2016). Mutations in the gene encoding α-synuclein (Polymeropoulos et al, 1997; Helferich et al, 2015; Majbour et al, 2016; Schonherr et al, 2016) represent autosomal dominant familial PD, and mutations in genes encoding parkin (Kitada et al, 1998; Cha et al, 2015), UCHL1 (Leroy et al, 1998; Maraganore et al, 1999), DJ-1 (Bonifati et al, 2003), PINK1 (Valente et al, 2004), and LRRK2 (Zimprich et al, 2004; Saha et al, 2015) cause autosomal recessive familial PD.…”
Section: Abnormal Protein Aggregation In Neurodegenerative Diseasesmentioning
confidence: 99%
“…Sporadic PD accounts for more than 90% of PD cases (Lang and Lozano, 1998), and only less than 10% of familial PD cases are caused by monogenic mutations (Benitez et al, 2016). Mutations in the gene encoding α-synuclein (Polymeropoulos et al, 1997; Helferich et al, 2015; Majbour et al, 2016; Schonherr et al, 2016) represent autosomal dominant familial PD, and mutations in genes encoding parkin (Kitada et al, 1998; Cha et al, 2015), UCHL1 (Leroy et al, 1998; Maraganore et al, 1999), DJ-1 (Bonifati et al, 2003), PINK1 (Valente et al, 2004), and LRRK2 (Zimprich et al, 2004; Saha et al, 2015) cause autosomal recessive familial PD.…”
Section: Abnormal Protein Aggregation In Neurodegenerative Diseasesmentioning
confidence: 99%
“…These structural features provide all requirements that meprin b must have to act as an ectodomain sheddase at the cell surface. Indeed, membrane-bound amyloid precursor protein (APP), for instance, is cleaved by meprin b, resulting in the release of sAPP-b fragments and neurotoxic Ab peptides (4,7,8). Many of the known substrates of meprin b have been identified by mass spectrometry (MS)-based proteomic approaches (9).…”
mentioning
confidence: 99%
“…Meprin ␤ knock-out also increased sAPP␤ in the soluble brain fraction as detected with a neoepitope-specific antibody, whereas conditioned medium from cells expressing APP SWE , which is a better substrate for BACE1 than wild-type APP (12), significantly altered the ratio of A␤2-40:A␤1-40 production, indicating direct competition between meprin ␤ and BACE1 for APP (27). Importantly, in the context of AD, A␤2-40 also showed increased aggregation propensity when compared with A␤1-40, implicating this species in the preferential production of oligomeric assemblies of A␤ (27). Still, in the brain, A␤2-X peptides are severalfold lower in abundance relative to A␤42 species.…”
Section: -Secretasementioning
confidence: 97%
“…Furthermore, cells expressing meprin ␤ produced significant amounts of A␤2-X even in the presence of a BACE1 inhibitor, whereas meprin ␤ inhibition significantly reduced its production (26). Further work has suggested that unlike BACE1, meprin ␤ cleaves APP at the cell surface and may directly compete with ADAM10 in vivo, as indicated by increased sAPP␣ in the soluble fractions derived from meprin ␤ knock-out mice brains (27). Meprin ␤ knock-out also increased sAPP␤ in the soluble brain fraction as detected with a neoepitope-specific antibody, whereas conditioned medium from cells expressing APP SWE , which is a better substrate for BACE1 than wild-type APP (12), significantly altered the ratio of A␤2-40:A␤1-40 production, indicating direct competition between meprin ␤ and BACE1 for APP (27).…”
Section: -Secretasementioning
confidence: 99%
See 1 more Smart Citation